2016
DOI: 10.3847/0004-637x/819/1/2
|View full text |Cite
|
Sign up to set email alerts
|

Apogee Kinematics. I. Overview of the Kinematics of the Galactic Bulge as Mapped by Apogee

Abstract: We present the stellar kinematics across the Galactic bulge and into the disk at positive longitudes from the SDSS-III APOGEE spectroscopic survey of the Milky Way. APOGEE includes extensive coverage of the stellar populations of the bulge along the midplane and near-plane regions. From these data, we have produced kinematic maps of 10,000 stars across longitudes of 0°< l < 65°, and primarily across latitudes of b | | < 5°in the bulge region. The APOGEE data reveal that the bulge is cylindrically rotating acro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
58
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 51 publications
8
58
0
Order By: Relevance
“…The kinematic maps show a (close-to) cylindrical rotation and a clear peak in velocity dispersion in the central regions that appears vertically elongated. These properties are in good qualitative (but not quantitative) agreement with the ones observed in the MW (Zoccali et al 2014;Ness et al 2016), in simulations (Qin et al 2015;Fragkoudi et al 2017a;Buck et al 2018b), and in similar external galaxies (Gonzalez et al 2016; Molaeinezhad et al 2016). In particular, the vertically elongated velocity dispersion 'peak' presented in Zoccali et al (2014) is clearly observed in the simulation once it is rescaled.…”
Section: Simulation Scalingsupporting
confidence: 78%
“…The kinematic maps show a (close-to) cylindrical rotation and a clear peak in velocity dispersion in the central regions that appears vertically elongated. These properties are in good qualitative (but not quantitative) agreement with the ones observed in the MW (Zoccali et al 2014;Ness et al 2016), in simulations (Qin et al 2015;Fragkoudi et al 2017a;Buck et al 2018b), and in similar external galaxies (Gonzalez et al 2016; Molaeinezhad et al 2016). In particular, the vertically elongated velocity dispersion 'peak' presented in Zoccali et al (2014) is clearly observed in the simulation once it is rescaled.…”
Section: Simulation Scalingsupporting
confidence: 78%
“…The APOGEE survey has observed a large number of 2MASS giants in the NIR, thereby also covering the low-latitude inner Galaxy. Combining the APOGEE and ARGOS data, Ness et al (2016) constructed latitude-combined rotation and dispersion profiles for the same metallicity bins, showing a smooth transition from the Bulge to the thin bar and disk. In these average profiles, A and B are very similar, with C showing higher dispersion and lower rotation.…”
Section: Kinematics With Metallicitymentioning
confidence: 99%
“…Because APOGEE was designed to include extensive and deep probes of the low-latitude Milky Way, including the highly extinguished regions of the disk and bulge, previously poorly studied regions of the Galaxy have now been opened up to extensive kinematical canvassing. As a result, a number of Galactic dynamical phenomena have already been discovered or reexamined with unprecedented statistical significance, including the discovery of a kinematically extreme population in the bulge , likely associated with the Galactic bar (Aumer & Schönrich 2015;Molloy et al 2015); a comprehensive analysis of the dynamics of the bulge (Ness et al 2016b); a new derivation of the circular velocity of the Sun afforded by the more global APOGEE view of disk kinematics ( Figure 24; Bovy et al 2012Bovy et al , 2015; and finally, an assessment of the power spectrum of non-axisymmetric velocity perturbations of the disk, of which most can be attributed to the action of the central bar . Figure 25, where the distribution of APOGEE targets projected onto the XY plane is displayed.…”
Section: Radial Velocities Across the Galaxymentioning
confidence: 99%